Mastery, Maladaptive Learning Behaviour, and Academic Achievement: An Intervention Approach - Ranellucci, John; Hall, Nathan; Muis, Krista; Lajoie, Susanne; Robinson, Kristy (Canadian Journal of Education/Revue canadienne de l'éducation, 2018)
The effects of three interventions designed to boost academic achievement among mastery-oriented students were evaluated on interest-based studying, social desirability, and perceived goal difficulty. Undergraduate students (N = 177) completed relevant self-report measures at the beginning and the end of the semester and were randomly assigned to one of three brief, web-based intervention conditions or a control condition. Multiple regression analyses showed the intervention conditions to consistently predict lower levels of interest-based studying, with these effects moderated by students’ prior achievement and mastery-approach goals. Qualitative analyses provide insight into the motivationally relevant processes elicited by the interventions.